The genesis of the Institute of Low Temperature and Structure Research of the Polish Academy of Sciences in Wrocław, Poland - Paweł E. Tomaszewski (Studia Historiae Scientiarum)
Institute of Low Temperature and Structure Research of Polish Academy of Sciences celebrated its 50th anniversary in November 2016. The paper presents the history of the Institute going backward to the history of other ten scientific institutions from which the Institute was finally founded in 1966. It shows the efforts of Prof. Roman Ingarden and Prof. Włodzimierz Trzebiatowski to establish a powerful center of physics and physico-chemistry of solid state in Wrocław.